El corazón de Jesús - Loayza, Marcos; Mendieta, Cacho, 1942-; Wilde, Maritza; Carpio Soriano, Melita del (Iconoscopio, 2003)
Following a heart attack, government worker Jesus finds himself unable to pay the hospital bills when his wife absconds with his savings. He is forced to try to con the insurance company into covering his costs.